Profitability, Good Corporate Governance, Dividend Policy, and Firm Value at ISSI - Rani Safitri; Rika Lidyah; Rachmania Rachmania (ETIKONOMI, 2022)
This study aims to determine the relationship between profitability, good corporate governance, dividend policy, and firm value from 2016-2018 in manufacturing companies at ISSI. This study uses classical assumption tests and path analysis. The results show that the board of commissioners has a significant negative effect on profitability and has no impact on firm value. The audit committee and dividend policy do not affect profitability and firm value. Profitability has a significant positive effect on firm value. Profitability mediates the impact of the board of commissioners and dividend policy but does not mediate the audit committee on firm value. This finding shows a relationship between variables that impact firm value. The implication of this research is to suggest that investors need to look at the company's prospects by paying attention to the company's value and analyzing the company's performance by considering the influencing factors. How to Cite:Safitri, R., Lidyah, R., & Rachmania. (2022). Profitability, Good Corporate Governance, Dividend Policy, and Firm Value at ISSI. Etikonomi, 21(1), 139-152. https://doi.org/10.15408/etk.v20i1.16524.